Upacara Nyawang di Desa Adat Batuyang Gianyar - Tisna Kurniawan, I Wayan; Poniman; Januariawan, I Gede; Suwadnyana, I Wayan; Seriasih, Ni Wayan (Jayapangus Press, 2023)
The implementation of the panca yajna ceremony will not be separated from the life of the Balinese people, as is the case with the Nyawang Ceremony which is carried out by the people of the Batuyang Traditional Village, Gianyar. The purpose of this study was to explore the concepts of Hindu teachings contained in the Nyawang Ceremony in Batuyang Traditional Village. The research method used is qualitative with data collection techniques using observation, interviews and literature study. The research results show that; 1) The form of the Nyawang ceremony is a series of yadnya ceremonies in which there are worship of Hulu and Teben. The Nyawang ceremony consists of stages, namely, the series of ceremonies, ceremonial devices or vehicles, ceremonial spells, and manggala ceremonies. 2) The function of the Nyawang Ceremony for the residents of Batuyang Traditional Village is generically a form of sraddha bhakti of the residents to the Creator and maintaining the natural balance of both Bhuana Agung and Bhuana Alit. The process of communication at the Nyawang Ceremony is very important to understand, because communication has a role in achieving the desired goals.